2012
DOI: 10.5539/ibr.v5n3p100
|View full text |Cite
|
Sign up to set email alerts
|

Can Country Image Change after Likable Incident? The Case of Chile Miners’ Rescue Operation and the Middle East Consumers

Abstract: Country image plays a key role in influencing consumers' perceptions towards products originating from foreign countries. Economic and commercial relations between countries in the Middle East region and South America have improved strongly in the last decade. However, there is a dearth of studies conducted in the Middle East countries regarding products sourced from South American countries. This study aims to explore how Chile miners' rescue operation has been perceived by Jordanians and how it has influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Giraldi and Ikeda (2009) argued that consumers’ evaluation of products from other countries can be influenced by their deeply rooted stereotype associated with these countries. Studies in international marketing (Chandrasen & Paliwoda, 2009; Ganideh, 2012) also showed a correlation between a nation’s economic status and the superiority of its products because consumers generally are in favor of products made from highly industrialized countries. However, with the complexity of globalized economy and more sophisticated division of labor, a product may be associated with multiple countries in terms of its manufacture, brand, design, assembly, and head office, which further complicates the issue of country-of-origin effects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Giraldi and Ikeda (2009) argued that consumers’ evaluation of products from other countries can be influenced by their deeply rooted stereotype associated with these countries. Studies in international marketing (Chandrasen & Paliwoda, 2009; Ganideh, 2012) also showed a correlation between a nation’s economic status and the superiority of its products because consumers generally are in favor of products made from highly industrialized countries. However, with the complexity of globalized economy and more sophisticated division of labor, a product may be associated with multiple countries in terms of its manufacture, brand, design, assembly, and head office, which further complicates the issue of country-of-origin effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on previous findings of country image’s influence on imported products (e.g. Chandrasen & Paliwoda, 2009; Ganideh, 2012; Samiee et al, 2016), it is hypothesized that all three components may affect people’s attitude and behavior related to Chinese products:…”
Section: Research Question and Hypothesesmentioning
confidence: 99%